The effect of green intellectual capital, conservatism, earning management, to future stock return and its implications on stock return - Sugiyanto Sugiyanto; Fitri Dwi Febrianti (Universitas Hayam Wuruk Perbanas, 2021)
This study aims to analyze the effect of Green Intellectual Capital, Conservatism, and Real Earning Management on Future Stock Returns and their Implications on Stock Returns on Mining companies listed on the Indonesia Stock Exchange Period 2014 - 2019. This type of research is quantitative research in which this research is done by explaining the results of data from the calculation of numbers that are calculated and analyzed. The analysis used in this research is regression analysis, where regression analysis estimates the magnitude of the coefficients resulting from a linear equation involving one independent variable to be used as a predictor of the value of the dependent variable. The results of this study indicate that Intellectual capital has a significant effect on future stock returns, Conservatism has a significant effect on future stock returns, earning management has a significant effect on future stock returns, Implications future stock return on stock returns. These findings indicate that in sample companies, future stock returns on stock returns have no implication.